Microsatellite markers for Saussurea polylepis (Asteraceae), a vulnerable continental island species endemic to Korea. (14th June 2019) - Yun, Seon A; Kim, Seung‐Chul
Abstract : Premise: Nuclear microsatellite markers were developed for Saussurea polylepis (Asteraceae), a vulnerable species with very limited distribution in a few southwestern continental islands of the Korean peninsula, in order to facilitate future population genetic studies. Methods and Results: Based on the Illumina sequence data, a total of 21 microsatellite primer pairs were designed and tested for their suitability. Nineteen of these primers, with two to 11 alleles per locus, were polymorphic in three natural populations of S. polylepis . The levels of expected and observed heterozygosity ranged from 0.000 to 0.842 and 0.000 to 0.933, respectively. Sixteen of these simple sequence repeat (SSR) markers were successfully cross‐amplified in five congeneric species, namely S. gracilis, S. grandifolia, and S. tanakae for all 21 loci, and S. maximowiczii and S. pulchella for 18 loci. Conclusions: The SSR markers developed here will be useful for future population genetic studies on S. polylepis and related species.